(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article provides information on the appropriate use of real models in the process of educational activities in preschool educational organizations, namely their role and importance in the educational activity of familiarization with the environment. In particular, it is shown that the process of using small studies in educational activities sets itself the following tasks: intensive development of logical thinking in the process of familiarization with nature, intensive use of real models in the process of educational activities, increasing the interest of students in conducting research in the process of educational activities. The article also provides a review of scientific research conducted within the framework of the topic